Duskward displacement of plasmoids and reconnection in the near-Earth magnetotail - Akimasa Ieda; Yukinaga Miyashita (Earth, Planets and Space)
Abstract Magnetic reconnection in the near-Earth magnetotail is responsible for explosive release of energy during substorms and auroral breakups. This near-tail reconnection was previously assumed to occur around the midnight meridian, where earthward flows were typically observed. Based on observations of tailward-moving plasmoids, the Geotail spacecraft mission discovered that the reconnection location was displaced toward dusk. This dusk preference is presumably caused by the Hall electric field, as was suggested later in simulations. However, recent spacecraft observations have indicated that the reconnection was displaced toward dawn, and not dusk, in Mercury’s magnetotail. In response to this controversy, our study aims to clarify the dawn–dusk location of fast plasma flows in the near-Earth magnetotail. Through a comprehensive reinterpretation and integration of previous statistical results, we found that the dusk preference is generally evident for tailward flows but is often absent for earthward flows. These results indicate that the statistical results of earthward flows are sensitive to event selection criteria. We conclude that the dawn–dusk location of earthward flow is statistically unclear at the time of substorm onset. Similarly, in the magnetotail of other planets, the dawn–dusk location of planetward flow may be sensitive to event selection criteria. Hence, reconnection may occur predominantly on the duskside in Mercury’s magnetotail. This hypothesis will be tested using observations of tailward-moving plasmoids by the BepiColombo Mio spacecraft, which will begin orbital observations of Mercury in the year 2026. Graphical Abstract